Aplikasi Peta Wisata Berbasis Android Kabupaten Pesawaran - Wartarius Wartarius; Renaldi Zainal Arifin; Muhammad Junaidi (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Tourism is a valuable aspect for a region, with the existence of tourist areas it can advance the welfare of the surrounding community. Pesawaran Regency has a very large tourism area, if the existing facilities and infrastructure are further developed, it is ensured that the increase in tourism in Pesawaran Regency will increase. The use of Information Technology can advance tourism areas, so that tourism areas can be known by tourists who want to visit Pesawran District. Tourist maps are built using the Android platform, and the method used is a data collection method that includes observation, interview, and literature studies. While the system development method used is the SDLC method (software development lifecycle), which is the waterfall method. The stages of development begin with needs analysis, system design, coding, testing of Program Implementation and maintenance. The tourist map application was developed with the concept of integrating tourist information with a mobile web base by using GPS and Map to find out the distance traveled and travel time.